AMBLE: Adjusting mini-batch and local epoch for federated learning with heterogeneous devices - Park, Juwon; Yoon, Daegun; Yeo, Sangho; Oh, Sangyoon (Journal of Parallel and Distributed Computing, 2022)
As data privacy becomes increasingly important, federated learning applied to the training of deep learning models while ensuring the data privacy of devices is entering the spotlight. Federated learning makes it possible to process all data at once while processing data independently from various devices without collecting distributed local data in a central server. However, there are still challenges to overcome for the system of devices in federated learning such as communication overheads and the heterogeneity of the system. In this paper, we propose the Adjusting Mini-Batch and Local Epoch (AMBLE) approach, which adaptively adjusts the local mini-batch and local epoch size for heterogeneous devices in federated learning and updates the parameters synchronously. With AMBLE, we enhance the computational efficiency by removing stragglers and scaling the local learning rate to improve the model convergence rate and accuracy. We verify that federated learning with AMBLE is a stably trained model with a faster convergence speed and higher accuracy than FedAvg and adaptive batch size scheme for both identically and independently distributed (IID) and non-IID cases.
Keywords: Central servers; Communication overheads; Federated averaging; Federated learning; Heterogeneous devices; Learning models; Local data; Local mini-batch SGD; Scalings; System heterogeneity; Federated averaging; Federated learning; Local mini-batch SGD; System heterogeneity